MODERN ASPECTS OF HUMAN PAPILLOMAVIRUS VACCINATION - O. S. Alyautdina; M. A. Darmostukova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
Human papillomavirus refers to DNA-containing viruses and infects the skin and mucosal epithelium. One common way is to change the  expression of cellular genes by integrating the viral genome into  cellular DNA. The reason for the resistance of HPV infection is the  presence of complex mechanisms of inhibiting the immune response  of the macroorganism. An important infectious agent involved in  carcinogenesis are human papillomavirus (HPV) viruses, which cause  a significant part of oncological diseases. Viruses create the  prerequisites for malignant cells by introducing an oncogene or  blockade of suppressor proteins in cells to disrupt the regulation of  cell division. Two proteins, E6 and E7, encoded by the DNA of the  virus, play a leading role in this process. More than 100 different types of HPV have been identified, and approximately one- third of them infect epithelial cells in  the genital tract. HPV is also  the cause of carcinoma of the penis, vulva, anus and contribute to  the occurrence of more than 40 % of oropharyngeal cancer. To date,  the most effective way to combat HPV infection is  immunoprophylaxis. To date, there are three commercially available  HPV vaccines: Cervarix®, Gardasil®, Gardasil®9. These three  vaccines effectively prevent HPV infections, causing the production of neutralizing antibodies that bind to viral particles and block their  entry into host cells. However, these vaccines are not effective in  eliminating pre-existing infections. Currently, there are no  therapeutic vaccines against HPV, approved for use in humans. The  review discusses the types of vaccines against HPV infection and the effectiveness of vaccination.